Two-dimensional SnO2 anchored biomass-derived carbon nanosheet anode for high-performance Li-ion capacitors. Issue 17 (8th March 2021) - Liu, Chang; He, Zeyin; Niu, Jianmin; Cheng, Qiang; Zhao, Zongchen; Li, Haoran; Shi, Jing; Wang, Huanlei
Abstract : In this work, we have fabricated lithium-ion capacitor using SnO2 /PCN as anode and waste coffee grounds derived PCN as cathode, which delivers good combination of high energy and power characteristics. Abstract : Lithium-ion capacitors (LICs) combine the advantages of both batteries and supercapacitors; they have attracted intensive attention among energy conversion and storage fields, and one of the key points of their research is the exploration of suitable battery-type electrode materials. Herein, a simple and low-cost strategy is proposed, in which SnO2 particles are anchored on the conductive porous carbon nano-sheets (PCN) derived from coffee grounds. This method can inhibit the grain coarsening of Sn and the volume change of SnO2 effectively, thus improving the electrochemical reversibility of the materials. In the lithium half cell (0–3.0 V vs. Li/Li + ), the as-prepared SnO2 /PCN electrode yields a reversible capacity of 799 mA h g −1 at 0.1 A g −1 and decent long-term cyclability of 313 mA h g −1 at 1 A g −1 after 500 cycles. The excellent Li + storage performance of SnO2 /PCN is beneficial from the hierarchical structure as well as the robust carbonaceous buffer layer. Besides, a LIC hybrid device with the as-prepared SnO2 /PCN anode exhibits outstanding energy and power density of 138 W h kg −1 and 53 kW kg −1 at a voltage window of 1.0–4.0 V. These promising results open up a new way to develop advanced anode materials with high rate and long life.